Effects of maternal mental health on prenatal movement profiles in twins and singletons. (8th June 2021) - Reissland, Nadja; Einbeck, Jochen; Wood, Rebecca; Lane, Alison
Abstract: Aim: Prenatal experiences, including maternal stress, depression and anxiety, form crucial building blocks affecting the maturation of the foetal central nervous system. Previous research has examined foetal movements without considering effects of maternal mental health factors critical for healthy foetal development. The aim of this research is to assess the effects of maternal mental health factors on foetal twin compared with singleton movement profiles. Method: We coded foetal touch and head movements in 56 ultrasound scans, from a prospective opportunity sample of 30 mothers with a healthy pregnancy (mean gestational age 27.8 weeks for singleton and 27.2 for twins). At the ultrasound scan appointment, participants completed questionnaires assessing their stress, depression and anxiety. Results: Maternal depression increased foetal self‐touch significantly. In foetal twins, maternal stress significantly decreased and maternal depression significantly increased other twin touch. Maternal mental health factors affected the head movements of twins significantly more than singletons, with maternal depression decreasing head movement frequency for twins significantly. Conclusion: These results indicate that maternal mental health might have an impact on types of body schemata formed in utero, in twin compared with singleton pregnancies. Future research needs to examine whether these prenatal effects affect postnatal differences in body awareness.